ANALISIS KEUNTUNGAN USAHA TAPE SUCIPTO DI KELURAHAN KLEAK KOTA MANADO - Nyariang Belen; Martha Mareyke Sendow; Sherly Gladys Jocom (AGRI-SOSIOEKONOMI, 2020)
The purpose of this study was to analyze how much profit from the Sucipto Tape business in Kelurahan Kleak, Manado City. The study was conducted in Kelurahan Kleak Lingkungan 4, Malalayang District, Manado City. This research was conducted for 3 months starting in September 2019 until November 2019. Primary data were collected by direct interview with the owner of the Sucipto Tape business. Data collected in the form of data on the selling price of tape products, production of tape produced in one month of production, production costs involve fixed costs (electricity costs and depreciation costs) and variable costs (transportation costs, costs of main raw materials, costs of supporting materials, fuel costs , packaging costs, labor costs). The data collected was then analyzed using Profit Analysis and Revenue Cost Ratio Analysis. The results showed that the Sucipto tape business in the Kleak Kelurahan of Manado City earned a monthly profit of Rp. 1.990.332,33. The R / C value of the Sucipto Tape Business in September 2019 of 1.52 shows a number> 1, so it can be concluded that this business was profitable.*eprm*